Other Modernisms: Recording Diversity and Communicating History in Urban West Africa - Uduku, Ola (Docomomo Journal, 2013)
Seminal publications on West African Architecture such as Kulterman’s New Architecture in Africa and the Architectural Review’s New Commonwealth Architecture came to define the African Modern Movement as it was understood internationally. This paper explores the specific context within which this new architecture developed and the actors that helped to shape it. Vaughan–Richards’ Ola–Oluwakitan House and Cubitt’s Elder Dempster Offices are analyzed in terms of their engagement with the socio-cultural context in which they were conceived, the site-specific Modernity of the former contrasting the corporate International Style response of the latter.